The Moderation Effect of Job Satisfaction on The Influence of Organizational Commitment and Competency on Lecturer Performance in Asahan District - Lubis, Fajar Rezeki Ananda (Jurnal Manajemen Dayasaing, 2024)
The quality of education is significantly impacted when a professor needs to do better in carrying out his obligations. Reviewing whether organizational commitment and competence affect lecturer performance is therefore crucial. This study was carried out in the Asahan Regency at multiple universities. There were 230 participants in the study's sample. The study's findings demonstrate that organizational commitment significantly and favorably affects the performance of lecturers in higher education in the Asahan Regency. Their dedication and competence positively and significantly impact the performance of lecturers in higher education at Asahan Regency. Organizational commitment has a favorable and significant moderating effect on lecturer performance regarding job satisfaction. The influence of competency on lecturers is positively and strongly moderated by job satisfaction.